Respon Fungsional Menochilus sexmaculatus Fabricius terhadap Aphis gossypii Glover - F. X. Wagiman (Jurnal Perlindungan Tanaman Indonesia, 1996)
Laboratory and field-cage experiments were conducted at the Universiti Pertanian Malaysia. Objective of the study was to determine the functional response of Menochilus sexmaculatus Fabricius (Coleoptera: Coccinellidae) predating on chilli aphid Aphis gossypii Glover (Homoptera: Aphididae). The larvae and adults of the predaceous coccinellid exhibited the Hulling's Type II functional response. A first instar of the coccinellid predating on single first instar of the aphid within 24.6 minutes in the laboratory and 16.8 minutes in the field. While a fourth instar and an adult of the coccinellid predating on single fourth instar of the aphid within 4.2 and 1.5 minutes respectively.